2007
DOI: 10.1103/physreve.75.011929
|View full text |Cite
|
Sign up to set email alerts
|

Spiral-wave dynamics depend sensitively on inhomogeneities in mathematical models of ventricular tissue

Abstract: Every sixth death in industrialized countries occurs because of cardiac arrhythmias such as ventricular tachycardia (VT) and ventricular fibrillation (VF). There is growing consensus that VT is associated with an unbroken spiral wave of electrical activation on cardiac tissue but VF with broken waves, spiral turbulence, spatiotemporal chaos and rapid, irregular activation. Thus spiral-wave activity in cardiac tissue has been studied extensively. Nevertheless, many aspects of such spiral dynamics remain elusive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
81
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 42 publications
7
81
0
Order By: Relevance
“…It is well known that a rotor can be locally stabilized due to anchoring to an inexcitable obstacle (4,25,26,35), i.e., process when a rotor attaches to the boundary of such an obstacle. Later, it was shown that rotors can anchor to other types of heterogeneities: ionic heterogeneities (30,31), blood vessels (40), pectinate (42), and papillary muscles (13). Also in Refs.…”
mentioning
confidence: 99%
“…It is well known that a rotor can be locally stabilized due to anchoring to an inexcitable obstacle (4,25,26,35), i.e., process when a rotor attaches to the boundary of such an obstacle. Later, it was shown that rotors can anchor to other types of heterogeneities: ionic heterogeneities (30,31), blood vessels (40), pectinate (42), and papillary muscles (13). Also in Refs.…”
mentioning
confidence: 99%
“…In general, it was shown that the presence of inhomogeneities in the medium not only stabilizes the spiral wave dynamics as shown in (Ikeda et al, 1997;Kim et al, 1999;Shajahan et al, 2007) but also might generate more complex dynamics, which implies that the presence of obstacles might induce a more dangerous arrhythmic regime than the one without the obstacle. Drift of a spiral wave had been considered only for planar boundaries (Yermakova & Pertsov, 1986) and inside circular domains (Mikhailov et al, 1994).…”
Section: Conclusion Limitations and Open Questionsmentioning
confidence: 99%
“…Examples of partially excitable obstacles are scar tissue (Starobin et al, 1996) or ionic heterogeneities (Starobin et al, 1996;Tusscher & Panfilov, 2002;Valderrábano et al, 2000), whereas examples of non excitable obstacles are arteries (Valderrábano et al, 2000) or the natural orifices in the atria (Azene et al, 2001). It has been observed that an obstacle in cardiac tissue might act as a stabilizer of spiral wave dynamics (Davidenko et al, 1992;Ikeda et al, 1997;Kim et al, 1999;Lim et al, 2006;Pertsov et al, 1993;Valderrábano et al, 2000), as it provides a transition between meandering spiral waves (Ikeda et al, 1997) or multiple spiral waves (Shajahan et al, 2007;Valderrábano et al, 2000) into a simple rotation spiral, which is attached to the obstacle. This 17 www.intechopen.com transition is clinically important because as it has been shown, fibrillation like activity changes to a tachycardia regime (Kim et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations